The Fire Services (Compensation) Regulations 1965 - Soskice, Frank (Her Majesty's Stationery Office, 1965)
STATUTORY INSTRUMENTS LOCAL GOVERNMENT, ENGLAND AND WALES LONDON GOVERNMENT The Fire Services (Compensation) Regulations 1965
ERAF: A6.SI.1965.563
Keywords: Statutory Instruments; local government; fire service